PERAN DINAS KESEHATAN DALAM MENGAWASI TOKO JAMU YANG MENJUAL JAMU TRADISIONAL DENGAN CARA MENCAMPUR JAMU TRADISIONAL DENGAN BAHAN KIMIA OBAT (Studi di Dinas Kesehatan Kota Malang) - Bagus Nanda Hutama (Kumpulan Jurnal Mahasiswa Fakultas Hukum, 2014)
BAGUSNANDAHUTAMA, BusinessCivil Law, Faculty ofLaw, University ofBrawijaya, August 2014, The Role ofHealth ServiceInOverseeingTheHerbShopBy Selling Traditional Herbal MedicineHerbs by Mixing traditional herbs with Medicinal Chemicals(Studies inHealth ServiceMalang), Indrati, SHMS;Djumikasih, S.H.M.H. This thesisdiscusses theroleandperformanceof MalangCity Health Departmentin conductingmonitored toanticipatecirculation oftraditionalmedicinethat containsorhas beenmixedwith chemicalsdrugs. The activity wasobviouslymotivatedby manytraditionaldrug discoverythathas beenmixedwitha chemicaldrug. Issues raisedishowthe roleof MalangCity Health Departmentin carrying outsurveillanceof the circulation oftraditional medicinethathas beenmixedwithMedicinal Chemicals, andbarriers experienced. This research usesempiricalresearchwithsociologicaljuridical. From theresults ofthe analysishas beendone, itcan be seen thatshapeof thesupervision conductedbythe City Healthof Malangisby conductinginspectionsanddotests onsamples oftraditional medicinesthat exist in everystoreshops sellingtraditional medicine, counselingandguidance toPerformbusinesses andconsumers. Their rolesinthecontrol policiesarealsosomeconstraints experiencedbythe unfortunateCity Health Department include, a lack of understandingabout thelack of understanding ofthe substance ofCity Health Department of MalangLawin force, lack ofhuman resourcesinCity Health Department of MalangCity Health Departmenttosupport theefficiencyof thesurveillanceprogramof traditionalmedicine,low level ofeducationandthe local economy, lack ofawarenessandknowledgebusinessesonregulationsregardingtraditional medicineandmedicinalchemicals. Advicefromthe authorthatCity Health Department of Malangcandomoreintensivemonitoring, for consumersandfor the general publicit is bettertobe more selectiveto understandall aspectsbefore taking anymedicationused as guidelinestraditional, thebusiness is expectedalwaysprioritizedbusinessethicsandconsumer safety. Keywords: City Health Department of Malang, ImplementationMonitoring, CirculationTraditional Medicine, Medicinal Chemicals.